Akayét Um Marup = Hikayat Um Marup = Epopée Um Marup - Po Dharma; Weber, Nicolas; Abdullah Zakaria Bin Ghazali; École française d'Extrême-Orient (Kuala Lumpur Kementerian Kebudayaan, Kesenian dan Pelancongan Malaysia, 2007)
Cham classical literature and manuscript.
Includes bibliographical references and index.
Malay and French, with original text in Cham.